NO-Dependent Mechanisms of Rhythmic Cold Exposures on Functional Architectonics of Microhemocirculatory Bed in Rat Brain - Lutsenko, D. G.; Marchenko, V. S.; Babiychuk, V. G. (Problems of Cryobiology and Cryomedicine, 2011)
Rhythmic cold exposures lead to increasing of nitrite ion concentration in rat blood serum and brain cortex, resulting in redistribution of blood in brain microcirculatory bed. Fractal analysis admits to give a quantitative assessment for this alteration.